2020
DOI: 10.1101/2020.06.12.146290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal isolation of potent near-germline SARS-CoV-2-neutralizing antibodies from COVID-19 patients

Abstract: 38The SARS-CoV-2 pandemic has unprecedented implications for public health, social 39 life, and world economy. Since approved drugs and vaccines are not available, new 40 options for COVID-19 treatment and prevention are highly demanded. To identify 41 SARS-CoV-2 neutralizing antibodies, we analysed the antibody response of 12 42 COVID-19 patients from 8 to 69 days post diagnosis. By screening 4,313 SARS-43CoV-2-reactive B cells, we isolated 255 antibodies from different time points as early 44 as 8 days post … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
158
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(182 citation statements)
references
References 42 publications
24
158
0
Order By: Relevance
“…We showed RBD-SpyVLPs to be strongly immunogenic in mice and pigs, inducing high titre neutralising antibody responses against wild type SARS-CoV-2 virus. This study confirms that the RBD is the key immunogenic domain for eliciting neutralising monoclonal antibodies against SARS-CoV-2, in line with studies showing that highly neutralising antibodies isolated from convalescent patients bind to the RBD 16,26,38,[40][41][42][43][44][45][46] . We showed that RBD-SpyVLPs are recognised by a panel of mAbs isolated from convalescent patients 26 binding to various epitopes on the RBD (Figure 2A).…”
Section: Discussionsupporting
confidence: 84%
“…We showed RBD-SpyVLPs to be strongly immunogenic in mice and pigs, inducing high titre neutralising antibody responses against wild type SARS-CoV-2 virus. This study confirms that the RBD is the key immunogenic domain for eliciting neutralising monoclonal antibodies against SARS-CoV-2, in line with studies showing that highly neutralising antibodies isolated from convalescent patients bind to the RBD 16,26,38,[40][41][42][43][44][45][46] . We showed that RBD-SpyVLPs are recognised by a panel of mAbs isolated from convalescent patients 26 binding to various epitopes on the RBD (Figure 2A).…”
Section: Discussionsupporting
confidence: 84%
“…Neutralizing antibodies were considered as an ideal medicine for prophylaxis and treatment of infectious diseases 33 . At present, several potent neutralizing Abs to SARS-CoV-2 have been promptly developed and being tested in clinical trials (clinicaltrials.gov NCT04497987, NCT04426695 and NCT04425629) for treating COVID-19 patients [12][13][14][15]17,[19][20][21]34,35 . These reports showed that even though neutralizing antibodies against SASR-CoV-2 could be obtained from convalescent patients, the success rate to discover potent neutralizing antibodies with therapeutic value remains unideal.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that related, potently neutralizing monoclonal antibodies that recognize the SARS-CoV-2 receptor binding domain (RBD) are often elicited in SARS-CoV-2 infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These antibodies have great potential to be clinically impactful in the treatment and prevention of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%